In the barren ground - White, Loreth Anne (Seattle : Montlake Romance, 2016)
"In the Barrens, a vast wilderness in northern Canada bordering the Arctic Circle, night consumes every hour of the winter. Humans are scarce; ferocious predators roam freely. Locals say spirits do, too. Rookie cop Tana Larsson doesn't mind the dark and quiet. Five months pregnant and hoping to escape the mistakes of her past, she takes a post in Twin Rivers, population 320. Maybe here she can find peace and community for her child. But with her superior out of commission, Tana becomes the sole police officer in 17,500 square miles. One bitter night, she gets a call about the fatal wolf mauling of two students, and the only way to reach the remote scene is to enlist the help of the arrogant, irritatingly handsome Cameron "Crash" O'Halloran, a local bush pilot with a shady reputation for smuggling and a past cloaked in shadow. When the macabre scene they uncover suggests violence much more sinister than animal, Tana must trust Crash if she wants to protect the town--and herself--from the evil that lurks in the frozen dark."--Amazon.com
Keywords: Policewomen -- Canada -- Fiction; Man-woman relationships -- Fiction; Pregnant women -- Fiction; Canada -- Fiction; Thrillers (Fiction); Detective and mystery fiction; Romance fiction